EXPLOITATION OF WOMEN IN THE NOVEL RE: BY MAMAN SUHERMAN: A MARXIST FEMINIST ANALYSIS - Papilon, Anthonius Laru; Anshari, Anshari; Faisal, Faisal (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This study aims to reveal the form of exploitation of women and the impact of exploitation on the existence of women in the novel Re: Karya Maman Suherman. The method used in this study is a descriptive qualitative research method. The data collection technique in this study was reading the entire contents of the novel RE: karya Maman Suherman. The data analysis technique for this study was carried out by data reduction, data presentation, and drawing conclusions. The results of this study found two aspects, the first form of exploitation which is divided into three forms of exploitation of women in the theory of Marxist feminism contained in the novel Re: Karya Maman Suherman, namely, the form of exploitation (1) commodification of women's bodies, (2) forms of economic limitations and limited choices, (3) power relations. Women are treated as commodities for economic gain, with their bodies used as valuable assets for the benefit of pimps and customers. Economic dependence and limited life choices increasingly imprison women in unfair conditions, where they only receive a small portion of the results of their work, while large profits are enjoyed by those who control them. Unequal power relations reinforce this system of exploitation, where physical violence, such as beatings and threats, are used to maintain dominance and prevent women from escaping the trap of the system.